Essays on Asset Pricing: Distress Risk and Stock Returns - Andreou, Christoforos K. (Department of Commerce, Finance and Shipping, Faculty of Management and Economics, Cyprus University of Technology, 2018)
Financial distress risk is one of the main types of risks that investors and practitioners have to mitigate nowadays. Despite the large body of literature on financial distress and its consequences, many important research questions remain unanswered. This dissertation contributes to this literature through three empirical asset pricing studies that examine the impacts of firm-specific and country-specific financial distress on stock price crashes, stock returns, and foreign investors’ returns among others. The first chapter investigates the relationship between the firms’ financial distress and future stock price crashes. Based on monthly changes of distress risk as captured by the Black-Scholes-Merton (1973, 1974) distance-to-default (DD) model, firms which experience an increase in distress risk are more prone to stock price crashes one-month ahead. Using 343,271 monthly observations for the period 1990-2015, I find that this strong positive relationship remains robust for alternative measures of distress risk and stock price crashes. Additionally, changes in distress risk can predict stock price crashes as far as four months ahead. More importantly, I show that the crash-distress relationship is more pronounced when the firms’ information asymmetry is higher, as captured by the firms’ accounting opacity, stock liquidity, and analysts’ dispersion. In the second chapter, I examine the effects of misvaluation on the well-documented negative relationship between distress risk and stock returns (distress risk anomaly). Findings indicate that distress risk is negatively related to stock returns only in the subset of most overvalued stocks, consistent with the mispricing explanations of prior studies (Dichev, 1998; Griffin and Lemmon, 2002). Moreover, after removing mispricing effects from distress risk, the distress anomaly disappears. The results are robust to alternative specifications of distress risk and mispricing measures. Lastly, the third chapter focuses on country-specific distress risk, the sovereign risk. More specifically, I examine the rate of return earned by global funds on equity investment in emerging markets (EMs) particularly the role played by sovereign credit risk. Changes in sovereign credit ratings (upgrades/downgrades) influence excess (over risk-free rate) returns earned by foreign investors: lower excess returns are associated with lower risk. The effect of credit upgrades and downgrades, however, is not symmetric. By contrast, credit outlook ix or credit watch announcements do not seem to influence foreign investors’ excess returns. When it comes to abnormal (risk-adjusted) returns, foreign investors treat the information contained in credit rating announcements differently from that in outlook/watch announcements. The differing effect of these two is not evident for the risk-adjusted returns of domestic stock market indexes. There is evidence, however, that the behavior of foreign investors significantly influences the risk-adjusted returns of EM stock market indexes.
Keywords: Distress risk; Stock price crash; Mispricing; Sovereign risk